Strontium and Zinc Co-Doped Mesoporous Bioactive Glass Nanoparticles for Potential Use in Bone Tissue Engineering Applications - Parichart Naruphontjirakul; Meng Li; Aldo R. Boccaccini (Nanomaterials, 2024)
Mesoporous bioactive glass nanoparticles (MBGNs) have attracted significant attention as multifunctional nanocarriers for various applications in both hard and soft tissue engineering. In this study, multifunctional strontium (Sr)- and zinc (Zn)-containing MBGNs were successfully synthesized via the microemulsion-assisted sol–gel method combined with a cationic surfactant (cetyltrimethylammonium bromide, CTAB). Sr-MBGNs, Zn-MBGNs, and Sr-Zn-MBGNs exhibited spherical shapes in the nanoscale range of 100 ± 20 nm with a mesoporous structure. Sr and Zn were co-substituted in MBGNs (60SiO2-40CaO) to induce osteogenic potential and antibacterial properties without altering their size, morphology, negative surface charge, amorphous nature, mesoporous structure, and pore size. The synthesized MBGNs facilitated bioactivity by promoting the formation of an apatite-like layer on the surface of the particles after immersion in Simulated Body Fluid (SBF). The effect of the particles on the metabolic activity of human mesenchymal stem cells was concentration-dependent. The hMSCs exposed to Sr-MBGNs, Zn-MBGNs, and Sr-Zn-MBGNs at 200 μg/mL enhanced calcium deposition and osteogenic differentiation without osteogenic supplements. Moreover, the cellular uptake and internalization of Sr-MBGNs, Zn-MBGNs, and Sr-Zn-MBGNs in hMSCs were observed. These novel particles, which exhibited multiple functionalities, including promoting bone regeneration, delivering therapeutic ions intracellularly, and inhibiting the growth of Staphylococcus aureus and Escherichia coli, are potential nanocarriers for bone regeneration applications.